Recursos didácticos en la enseñanza-aprendizaje de los estudiantes de básica elemental de la Unidad Educativa Particular Cordillera, - Sánchez Lozano, Carla Lorena (2022)
Teaching resources have always been one of the main tools to generate significant learning in students, not only because they provide the opportunity to materialize content, but also because they awaken creativity, curiosity and imagination in the learner. In this context, the present investigation has as general objective to determine the incidence of the didactic resources in the teaching-learning of the elementary school students of the Cordillera Private Educational Unit. For this, the approach used was the quantitative one with a descriptive design, in which 38 students belonging to Elementary School participated, to whom a questionnaire was applied to identify the importance and use of didactic resources in the subject of social studies; and, through the inductive method, it was determined that there is a great influence of didactic resources on student learning, therefore they must be functional, visually attractive, easy to use, safe, useful for group and individual work and according to your age. It is concluded that, in the teaching-learning process, using a didactic resource is an effective way for the student to learn in a more meaningful and real way, taking into account its usefulness and manipulation. Keywords: didactic resources, strategies, motivation, skills, structural elements.